Improving communication and creativity in elementary civics: A PjBL action research on unity in ethnic diversity - Nofitasari, Nofitasari; Mubarok, Husni (STAI Auliaurrasyidin Tembilahan, 2025)
This study addresses the low communication skills and creativity among third-grade students at MI NU Mafatihul Ulum Sunggingan Kudus, attributed to conventional teacher-centered learning methods. To enhance student engagement, this research implements the Project-Based Learning (PjBL) model in Civic Education (PPKn), focusing on unity in ethnic diversity. Employing a convergent mixed-method design, the study combines qualitative data (observations, interviews) with quantitative pre/post-test questionnaires analyzed via t-test. Conducted as a two-cycle Classroom Action Research (CAR), each cycle comprised planning, implementation, observation, and reflection. Participants included 29 students (15 female, 14 male). Data were collected through observations, interviews, documentation, and evaluations of discussions and worksheets, then analyzed via data reduction, triangulation, and Paired-T Test. Results demonstrated moderate improvements: communication scores rose from 81.07 (Cycle I) to 81.97 (Cycle II), while creativity increased from 86.31 to 91.17. The Paired-T Test confirmed statistical significance (p < 0.05), indicating PjBL’s effectiveness in fostering 21st-century skills. These findings underscore PjBL’s potential as a student-centered approach to elevate communication and creativity in Civic Education.